Effects of the manufacturing process on fracture behaviour of cast TiAl intermetallic alloys (Fracture and Structural Integrity, 2013)
The ? -TiAl based intermetallic alloys are interesting candidate materials for high-temperature applications with the efforts being directed toward the replacement of Ni-based superalloys. TiAl-based alloys are characterised by a density (3.5-4 g/cm3) which is less than half of that of Ni-based superalloys, and therefore these alloys have attracted broad attention as potential candidate for high-temperature structural applications. Specific composition/microstructure combinations should be attained with the aim of obtaining good mechanical properties while maintaining satisfactory oxidation resistance, creep resistance and high temperature strength for targeted applications. Different casting methods have been used for producing TiAl based alloys. In our experimental work, specimens were produced by means of centrifugal casting. Tests carried out on several samples characterised by different alloy compositions highlighted that solidification shrinkage and solid metal contraction during cooling produce the development of relevant residual stresses that are sufficient to fracture the castings during cooling or to produce a delayed fracture. In this work, crack initiation and growth have been analysed in order to identify the factors causing the very high residual stresses that often produce explosive crack propagation throughout the casting.
Keywords: Titanium aluminides